2015
DOI: 10.1097/qai.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Abundance, Size, and MicroRNA Content of Plasma Extracellular Vesicles in Viremic HIV-1+ Patients

Abstract: Background:Because of factors only partly understood, the generalized elevated immune activation and inflammation characterizing HIV-1–infected patients are corrected incompletely with antiretroviral therapy (ART). Extracellular vesicles (EVs) including exosomes and microvesicles released by several cell types may contribute to immune activation and dysfunction. EV size, abundance, and content appear to differ according to infection phase, disease progression, and ART.Methods:We examined whether the size of EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
95
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 42 publications
8
95
1
Order By: Relevance
“…This phenomenon is not limited to HBMEC as it was shown that monocyte-derived macrophages infected with HIV-1 also secreted ECV in a larger amount (Kadiu et al 2012). These findings were also confirmed in human samples where both ECV number and size were increased in the plasma of HIV-1 positive ART-naive patients when compared to ART-suppressed patients, elite controllers, or healthy control subjects (Hubert et al 2015). The mechanism of increased ECV release by HIV-1 may be related to blocking the vesicle tethering by the protein tetherin, a process that can result in the facilitation of vesicle release.…”
Section: Discussionmentioning
confidence: 56%
“…This phenomenon is not limited to HBMEC as it was shown that monocyte-derived macrophages infected with HIV-1 also secreted ECV in a larger amount (Kadiu et al 2012). These findings were also confirmed in human samples where both ECV number and size were increased in the plasma of HIV-1 positive ART-naive patients when compared to ART-suppressed patients, elite controllers, or healthy control subjects (Hubert et al 2015). The mechanism of increased ECV release by HIV-1 may be related to blocking the vesicle tethering by the protein tetherin, a process that can result in the facilitation of vesicle release.…”
Section: Discussionmentioning
confidence: 56%
“…However, EVs produced by HIV-1-infected cells contain fragments of viral RNA [7] and viral proteins such as Nef [8] and Gag [9] (although another study did not find Nef to be associated with EVs [10]). HIV infection may alter the number and size of EVs as well as the host microRNA and proteins contained in EVs, which in turn may have implications for immune activation and HIV-1 pathogenesis [11][12][13][14]. In the setting of HIV-1 infection, EVs containing viral or host components may contribute to or exacerbate other conditions, such as HIV-1-or opiate-mediated neuron damage [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge about miRNAs, and particularly their relation with HIV, is growing and may provide future new tools for HIV-infected patients manage. For instance, some studies point to the possible usefulness of some miRNAs as biomarkers of disease progression, inflammatory state, and response to therapy [1,4,13]. Moreover, the use of some of them as antiviral treatment is studied.…”
mentioning
confidence: 99%
“…During this process microvesicles are released into the extracellular compartment transmitting pro-inflammatory signals to other cells [18]. Their mRNA and miRNA content is associated with the cells activation state as well as their origin [13]. miRNAs have been related to the production of interleukins (IL-10/Let-7; IL-6/miR-21, miR-122, miR-200a; IL-21/miRNA-29, miR-146a, miR-155) [4,5,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation